OPTIMUM DIMENSIONING OF INTERCONNECTIONS BETWEEN SOME GSM OPERATORS IN NIGERIA USING ERLANG B MODEL (FUDMA JOURNAL OF SCIENCES, 2022)
In the research, development, design and operation of telecommunication and computer networks, the important problems are determining the optimum configuration and dimensions of the system’s capacity for providing a given performance or Grade of Service (GoS). It would be uneconomical if exclusive resources such as switching and transmission facilities were dedicated to each customer. Therefore a pool of facilities is provided in common for a number of customers, and thus situations can arise in which a customer has to wait for connection, due to shortage of resources. Hence, it is required to evaluate such GoS quantitatively, and clarify relations between the GoS and the amount as well as configuration of the telecommunications facilities. In this paper, the Erlang B model coupled with Siemens Normal and High Load formulae are used to determine the optimum network capacity based on detailed user behavior and demanded quality of service parameters in an overall telecommunication system. As a benchmark, 18 months teletraffic data for interconnections between Networks A to F in Nigeria was utilized and Microsoft Excel was used for the analysis of the data. The performance level of the system has been calculated according to the International Telecommunications Union Standards (ITU-T) criteria. The results showed a Call Completion Rate (CCR) of 63% and the Answer Seizure Ratio (ASR) of 23% which were below the then standard values of 75% and 55% respectively. The result shows that the interconnections were not optimum. Some were over dimensioned and some were under dimensioned. Comparing with the
Keywords: Call Completion Rate (CCR), Answer Seizure Ratio (ASR), Erlang and Grade of Service (GoS)